Bibliometric Analysis: Utilization of Artificial Intelligence to Support Office Performance - Akbar, Rasona Sunara; Fathia, Vita Nurul; Hamdi, Muhammad Arif; Pujang, Seno Setya; Rosmaya, Mila; Bakhtiar, Masdar (Green Publisher Indonesia, 2024)
Artificial Intelligence (AI) has experienced rapid development in recent years. In the current era of globalization, research on the use of AI to support the implementation of tasks has urgency to be raised in the scientific realm. This article aims to explore the study of the utilization of AI in the field of organizational performance. This study uses bibliometric analysis to review all articles related to the theme in the leading Scopus database. The search was carried out on Wednesday, March 13, 2024, at 16.50 WIB, and resulted in 13 documents related to